Implementation of intensive care outreach: nurses and junior doctors’ knowledge, attitude and practice in risk assessment and responses to deteriorating patients - Ruslan, Rusila; Mohamed Ludin, Salizar (2015)
Background: Nurses and Junior Doctors play an important role in providing care to patients. Their knowledge, attitude and practice in assessing deteriorating patient are crucial. Lately, the incidence of deteriorating patient is worriedly especially in medical ward setting. In Malaysia, for the year 2013 it’s been reported that 47.4% deteriorating patient from total Intensive Care Unit admission were from the medical ward. Aim: The aim of this study is to determine nurses’ and junior doctors’ knowledge on assessment and treatment, attitude and practice towards assessing deteriorating patient in the medical ward and association among the variables. Method: A cross-sectional survey was used to collect data among nurses in medical wards in three Malaysian tertiary hospitals in the East Coast. Data was analyzed using SPSS 22.0 for descriptive and inferential analysis. Findings: Respond rate for this study is 79.5%. It was shown that nurses and junior doctors have good attitude and practice in assessing deteriorating patient and emergency pharmacotherapy. However, they had poor knowledge in assessing deteriorating patient. Respondents’ age does have an association with knowledge, attitude and practice in assessing deteriorating patient and also knowledge in emergency pharmacotherapy. Conclusion: Nurses and junior doctors need to develop more knowledge in assessing deteriorating patient even though they have a good attitude and good practice in assessing deteriorating patient as well as knowledge in emergency pharmacotherapy.